AEE for Multifunctional Resource Rooms: Legal, Pedagogical and Organizational Aspects (Research, Society and Development, 2022)
Inclusive education is a right guaranteed in the Federal Constitution for all students and the realization of this right must be fulfilled by education networks, indiscriminately. The present study deals with a bibliographical research about the Specialized Educational Assistance (AEE), with emphasis on the Multifunctional Resource Rooms (SEM), the legal, pedagogical and organizational aspects of this teaching modality. The Multifunctional Resource Rooms are the most widespread spaces for carrying out Specialized Educational Services (AEE). In them, teacheres with specialized training act as important mediators between the target audience of Special Education students, their families and teachers in the common classroom. In this institute, this article brings reflections and presents the main normative landmarks linked to the trajectory of the Resource Rooms. Methodologically, the article is based on authors such as Mendes (2021), Quadros (2020), Brazil (2010) and Dubuc (2015), with the research studies indexed in the databases: Coordination for the Improvement of Higher Education Personnel (Capes), Google Scholar and Scientific Electronic Library Online (Scielo). It was noticed that the implementation of multifunctional resource rooms in common schools of the public education network meets the need to promote the conditions of access, participation and learning of students target audience of special education in regular education, enabling the provision of educational service specialized, not a substitute for schooling. In summary, all special education students must be enrolled in common classes, in one of the stages, levels and modalities of basic education, with AEE offered in the opposite shift to regular education.